Recent Advances in Analytical Method Development and Validation for Simultaneous Estimation of Atorvastatin and Etoricoxib Using UV-Vis Spectrophotometry: A Comprehensive Review - Gulati, Puja; Bhagat, Tania (Journal of Neonatal Surgery, 2025)
UV-Vis spectrophotometry functions as a popular analytical technique that pharmaceutical analysis adopts intensively for API quantity determination and formulation quality monitoring. This examination explores the application of UV-Vis spectrophotometry to simultaneously determine atorvastatin and etoricoxib which are pharmaceutical agents used in cardiovascular disease and inflammatory disorder treatment. Molecules inside complex mixtures can be measured using the absorption technique because the technique enables absorption of specific light wavelengths. Spectral wavelength overlaps create interference with excipients elements along with introducing matrix interferents thus posing difficulties to simultaneous estimation methods. A combination of derivative spectrophotometry techniques with both multivariate calibration and chemometric methods enhances the accuracy and sensitivity and precision of UV-Vis spectrophotometry measurements. The latest advancements in simultaneous analysis of atorvastatin along with etoricoxib in complicated pharmaceutical materials and biological specimens create precise and controlled determination methods. The advancement of UV-Vis spectrophotometry through research resulted in portable device and microfluidic system creation which enabled extended on-site analysis capabilities together with point-of-care testing potential. The review details the operation of this method throughout pharmaceutical quality controls and stability testing and bioequivalence examinations and bioanalytical work focused toward pharmaceutical product protection. Future developments in UV-Vis spectrophotometry will focus on improving detection sensitivity together with lowering interferences and enhancing mobility as part of green chemical methods and standardized analytical procedures worldwide. The future development agenda aims to strengthen UV-Vis spectrophotometry as an indispensable pharmaceutical analytical instrument.